2022
DOI: 10.15562/bmj.v11i3.3596
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation in suppressing Troponin I and NT-proBNP level in breast cancer patients with 5- fluorouracil, adriamycin, and cyclophosphamide chemotherapy

Abstract: Background: Breast cancer is a malignancy originating from breast tissue, where chemotherapy is one of the choice therapy. Doxorubicin, 5-fluorouracil, and cyclophosphamide (FAC) are the most commonly used combination of chemotherapy. One of the side effects of chemotherapy is cardiotoxicity. Multiflora honey prevents cardiotoxic effects through its flavonoids and polyphenols compounds. The aim of this research is to analyze the effectiveness of adding honey in preventing cardiotoxic effects in breast cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was concluded that efavirenz was associated with an ELISA which was sensitive to detecting estradiol [22]. Hence, it is plausible that efavirenz exerts an effect similar to estradiol within the human body, promoting the expansion of breast tissue and contributing to the development of gynecomastia [23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that efavirenz was associated with an ELISA which was sensitive to detecting estradiol [22]. Hence, it is plausible that efavirenz exerts an effect similar to estradiol within the human body, promoting the expansion of breast tissue and contributing to the development of gynecomastia [23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%